Realization of Logic Functions Using Switching Lattices Under a Delay Constraint - Aksoy, Levent; Akkan, Nihat; Sedef, Herman; Altun, Mustafa (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Switching lattices, consisting of four-terminal switches, present an alternative structure for the realization of Boolean logic functions. Although promising algorithms have been introduced to find a realization of a logic function using a switching lattice with the fewest number of four-terminal switches, the delay of a switching lattice has not been examined yet. In this article, we generate a switching lattice using a recently proposed CMOS-compatible four-terminal device model and formulate the delay of a path in a switching lattice. It is observed that the delay of a design realizing a logic function on a switching lattice heavily depends on the number of four-terminal switches in the critical path. With this motivation, we introduce optimization algorithms, called PHAEDRA and TROADES, which can find the realization of a logic function on a switching lattice with the fewest number of switches under a delay constraint given in terms of the number of switches in the critical path. While PHAEDRA is a dichotomic search algorithm that can obtain solutions with a small number of switches on small size logic functions, TROADES is a divide-and-conquer method that can find a solution using less computational effort and can easily handle larger size logic functions with respect to PHAEDRA. The experimental results show that the proposed algorithms can reduce the delay of a lattice realization of a logic function significantly at a cost of an increase in the number of switches. They can explore alternative lattice realizations of a logic function by changing the delay constraint, enabling a designer to choose the one that fits best in an application.
Keywords: Lattices; Delays; Logic functions; Switches; Logic gates; Switching circuits; Binary search; divide and conquer; Elmore delay; emerging technologies; four-terminal switch; logic synthesis; satisfiability (SAT); switching lattice; Computer Science; Engineering